Diagnosis and treatment of vascular cognitive disorders - V. V. Zakharov (Klinicist)
Cognitive impairment (CI) usually is the earliest and most prevalent manifestation of cerebral vascular disease. Post stroke CI may have different clinical presentation depending on location of vascular lesion, so appropriate temporal association of CI onset with the event of stroke is of most important diagnostic value. Non-stroke (subcortical) variant of cerebral vascular disease usually is associated with small vessel disease. CI in subcortical variant is characterized with attention and executive functions deficit, frequently in combination with emotional disorders, postural instability and gait disturbances of frontal origin. Presence of vascular CI means essential need of thorough vascular risk factor (arterial hypertension, dyslipidemia, diabetes etc.) control. Vasotropic agents are prescribed with pathogenic purposes. The article presents clinical experience of nicergoline treatment of patients with vascular CI of different severity.